2021
DOI: 10.3389/fphar.2021.594586
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Skin Incisional Wound Healing With Intracellular ATP Delivery via Macrophage Proliferation and Direct Collagen Production

Abstract: This study sought to use a newly developed intracellular ATP delivery to enhance incisional wound healing to reduce surgical wound dehiscence and to explore possible mechanism for this effect. Thirty-five adult New Zealand white rabbits were used. Skin incisions were made on the back and closed. ATP-vesicles were mixed with a neutral cream for one side of the wounds while the neutral cream alone was used on the other side of the wounds. Laser speckle contrast imaging (LSCI), biomechanical, histological, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…Elastin has only been demonstrated to be present after these wound stages have progressed, in some cases months after this proliferative event [ 53 , 67 , 121 ]. Instead, collagen provides tensile strength to the skin and is mostly secreted into the healing wound space in a disorganized way, lacking structural integrity [ 17 , 122 ].…”
Section: Proliferationmentioning
confidence: 99%
“…Elastin has only been demonstrated to be present after these wound stages have progressed, in some cases months after this proliferative event [ 53 , 67 , 121 ]. Instead, collagen provides tensile strength to the skin and is mostly secreted into the healing wound space in a disorganized way, lacking structural integrity [ 17 , 122 ].…”
Section: Proliferationmentioning
confidence: 99%
“…However, SLO-induced membrane pores also result in the loss of cellular components, which probably impacts cellular metabolism in an unknown way. In this study, we used an ATP-encapsulated liposome 59 , 60 , 61 to restore intracellular ATP levels in mTORC2 deficient γδ T cells through membrane fusion. We showed that reconstitution of ATP in mTORC2-deficient γδ T cells fully restored IL-17 production with increased c-Maf and RORγt expression, suggesting that ATP may function as a metabolite directly interacting with transcription factors essential for γδT17 functional acquisition during development.…”
Section: Discussionmentioning
confidence: 99%
“…During the remodeling stage, the fibroblast continues to produce collagen 155 , 156 , and the level of collagen type III declines with time and is gradually replaced by collagen type I 157 , 158 . A recent study found the MSC-exos dose-dependent effect on the migration and proliferation of normal and diabetic chronic wound fibroblasts.…”
Section: Introductionmentioning
confidence: 99%